Identifikasi Dan Mitigasi Risiko Rantai Pasok Susu Sapi Pada Peternakan Sapi Di Desa Singosari, Kecamatan Mojosongo, Boyolali - Krismiyanto, Krismiyanto; , Hafidh Munawir, S.T., M.Eng (2016)
Efforts to increase the milk production must be supported by effective management of supply chains and efficient. Research conducted in the village of Singosari there are five elements of the supply chain is the level of suppliers cows, cattle breeders, collectors milk, milk cooling industry and retailers. The purpose of this study was to identify the risk of cow's milk and its supply chain risk mitigation plan. The benefits of the study is to provide data and information on the risk in the supply chain activity and risk remediation strategies in order to reduce or minimize the impact of the risk posed. The data collection phase is done with interviews, questionnaires and documentation to the parties involved in the supply chain flow of cow's milk. Data processing method using a combination of methods FMEA with tools House Of Risk (HOR). Stages that of the HOR there are two stages, stage 1 is used for the identification of risks while the second stage is used HOR risk management. The results of the risk identified as many as 29 risk while as many as 44 agents risk the risk, then used as inputs in the stage HOR 1. Processing of data obtained priority risk agents were 7 risk based on the value of ARP (Aggregate Risk Potential) which is included in the high category. The results of the seven priority risk agents will now be carried out actions risk mitigation strategies. Handling risks with HOR 2 obtained 18 mitigation actions by considerations of effectiveness, resources and level of difficulty. The final stage of discussion contains a description of the implementation of risk mitigation strategies that are expected to reduce the risk of significant problems. Keywords: House Of Risk, Supply Chain, Risk, Milk Cows,